Development Of Interactive Learning Multimedia Based On Canva In Vocational Subject Of Culinary - Novri Wahyuni; Elida Elida; Kasmita Kasmita; Dony Novaliendry (JETL (Journal of Education, Teaching and Learning), 2025)
Students with mild intellectual disabilities often face challenges in understanding abstract concepts and require specialized learning tools that support visual and interactive engagement. This study aimed to develop and evaluate the validity, practicality, and effectiveness of a Canva-based Interactive Learning Multimedia (ILM) designed specifically for vocational culinary education at SLB Negeri 1 Padang. Employing the Research and Development (R&D) method, this study involved expert validation, user practicality testing, and effectiveness analysis using quantitative techniques. Content and media validation were conducted by six experts using the Aiken’s V formula, practicality was assessed by one teacher and five students through questionnaires, and effectiveness was tested using normality, homogeneity, T-test, and effect size calculations with SPSS 27. The findings revealed that the ILM was highly valid, with average Aiken’s V scores of 0.97 (material experts) and 0.92 (media experts). Practicality scores from both students (3.87) and teachers (3.85) classified the media as very practical. Statistical analysis showed that the data were normally distributed and homogeneous. The T-test results demonstrated a significant difference in learning outcomes (t = 4.382 > t-table = 2.306; p < 0.05), indicating the effectiveness of the media. Furthermore, the effect size (Cohen's d = 2.8) suggested a very large effect on student performance. In conclusion, the Canva-based Interactive Learning Multimedia is a valid, practical, and highly effective tool to enhance vocational learning outcomes for students with mild intellectual disabilities. This innovation is recommended for broader implementation and further development in inclusive education settings.